Optimal policies of well completion and production wiht respect to coning effects for different types of reservoirs - Acurero Salas, Luis (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
Given a reservoir containing hydrocarbons, with dimensions and properties defined completely for reservoir and fluids; the problem is to maximize the present value of hydrocarbons removed from the reservoir through its economic life, by choice of the completion and production poliey to be used during the económic life of wells drílled in th8t reservoir. It is subject to constraints of production and boundary conditions for the reservoir . The problem is solved in two stages. First, a three-phases semianalytie single well model is formulated in order to determine the reservoiT response to any completion and production policy. This model assumes that the cone of water and gas can be represented as a succession of steady -states. Second, an optimization model based in the discrete version of the Maximum principie of Pontryagin, and the Fibonacci search method is formulated to determine the optimal production ”“and completion -poILey that will be used through the economic life of the wells.